Validation of the Arabic version of the Launay-Slade Hallucination Scale Extended: A population-based online survey in Saudi-Arabia - Haya Althuwaini; Georg Meyer; Ryan Ward; Henry Meyer (PLoS ONE, 2026)
Hallucinations occur when individuals perceive sensory events as real despite the absence of external stimuli. The Launay-Slade Hallucination Scale Extended Version (LSHS-E) is a validated measure for assessing hallucination proneness and has been adapted into several languages. Numerous studies worldwide have examined the factor structure of the LSHS-E, yet none have focused on the Arabic language. This study, conducted in Saudi Arabia, aimed to validate the Arabic version of the LSHS-E and explore its factor structure in an Arabic-speaking population. Following translation and back-translation, the Arabic LSHS-E was distributed to a Saudi Arabian general population sample (n = 428) via the Qualtrics Platform. Reliability was confirmed with high internal consistency (Cronbach’s alpha = 0.916; 95% CI: 0.904–0.927). Confirmatory factor analysis indicated that a four-factor model—comprising intrusive thoughts, vivid daydreams, multisensory HLEs, and auditory and visual HLEs—provided the best fit for the data (CFI = 0.93, RMSEA = 0.07, SRMR = 0.05). Positive correlations between LSHS-E scores and psychotic symptoms measured by the positive subscale of the Community Assessment of Psychic Experiences (PCAPE) supported convergent validity (r s = 0.55, p < 0.001). Sociodemographic analyses revealed that younger age (β = −5.30, p = 0.028) and lower income (β = −6.92, p = 0.028)were significant predictors of higher hallucination proneness scores. Our findings reveal response patterns and factor structures consistent with those observed in other languages and cultural contexts. The validated Arabic LSHS-E provides a reliable tool for studying hallucination proneness in Arabic-speaking populations.